Syed Sajjad Husain - Hasan, Md. Mahmudul (Asiatic Society of Bangladesh, 2011)
Syed Sajjad Husain was born in the village of Alokdia in what is now Magura district in Bangladesh in 1920. He obtained an MA degree in English literature from the University of Dhaka in 1942, securing first class first position. He completed his doctoral studies at Nottingham University in England and was awarded a PhD degree in 1952 for a research on Joseph Rudyard Kipling (1865-1936) and his treatment of India. In his PhD thesis, Husain critiqued the British author’s imprecise knowledge of the social and religious life of the subcontinent by referring to some of the Nobel laureate’s works especially Kim. Importantly, Husain is arguably the first Muslim of the subcontinent to obtain a PhD in English literature from a British university. Syed Sajjad Husain started his teaching career at Calcutta Islamic College in 1944. From 1948 to 1969 he taught at the English Department of Dhaka University where he worked as a Professor and the Head of the Department from 1959 to 1969. He was then appointed the Vice-Chancellor of Rajshahi University in 1969, but was transferred to Dhaka University in 1971 to become its Vice-Chancellor during the country’s liberation war period. However, his stance for the unity of Pakistan during the liberation war of the then East Pakistan (now Bangladesh) earned him huge controversy and disrepute, for which he had to suffer physical assaults and imprisonment and finally live in exile for a number of years after the country’s independence. Husain was a Fellow of the Claire Hall at Cambridge University, England for a period of three months in 1975. He also worked as a professor of English at Ummul Qura University in Makkah from 1975 to 1985 when he retired from his active teaching career. He came back to Bangladesh in the late 1980s to live permanently and passed away in Dhaka in 1995. Apart from his specialist knowledge of Bangla and English languages and literatures, he had a good command of Arabic, Urdu, Hindi and Persian languages and literatures. However, he wrote many works predominantly in English, and few pieces in Bangla.